Kramers–Kronig Analysis Of Infrared Reflectance Spectra With A Single Resonance (Jurnal Teknologi (Sciences & Engineering), 2012)
respectively. Key words: Kramers-Kronig analysis, infrared reflectance spectroscopy, optical phonon modes